Challenges of teaching human anatomy in Medical schools: a narrative literature review (Research, Society and Development, 2022)
Introduction: although the study of human anatomy is a fundamental subject in the medical course, there are some difficulties in learning it, and this is related to the scarcity of corpses, inadequate anatomical parts, lack of attention and motivation on the part of students, little student familiarity with anatomical terminologies and lack of use of active technologies and methodologies in teaching. Objective: to discuss the main challenges of teaching Human Anatomy in medical schools. Methodology: this is a narrative literature review. The research was carried out through access to the National Library of Medicine, Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO Information Services. Results and discussion: among the main challenges, we highlight the obstacles caused by bureaucracies related to the availability of corpses, the investment in technologies related to the high cost, as well as the difficulty in memorizing the large number of atypical names by the students, added the passive methodology applied by most faculties, with a reduced specific workload for the study of anatomy. Final considerations: it is necessary to adapt the significant portion of medical courses that have not yet updated the teaching methodology, to one that encourages the active search associated with studies of the anatomy of the human body, associated with clinical practice, thus increasing the workload of this discipline, in order to attract the interest of students in a more resolute way, given the viable opportunities available today.